2015
DOI: 10.1149/06801.1121ecst
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Tailored Nickel Nano-Catalyst Layer for Internal Reforming Hydrocarbon Fueled SOFCs

Abstract: Conventional Ni cermet anodes suffer from carbon deposition when they are directly used with hydrocarbon fuels due to the negative effects of pyrolysis and Boudouard reactions. In this work, the use of a non-stoichiometric perovskite, La0.8Ce0.1Ni0.4Ti0.6O3, as a reforming layer in reducing atmospheres led to the surface being highly populated with homogeneously exsolved Ni nano particles. This catalyst layer was applied to Ni-GDC anode supported and ScSZ electrolyte supported cells to prevent carbon depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…21 To investigate this, LSTN compositions with various A-site decient stoichiometries and with varying surface conditions were investigated with respect to the resulting morphology and microstructure aer a reduction for 2 h at 900 C in 5 vol% H 2 in Ar (Fig. 7).…”
Section: Materials Concept For Novel Sofc Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“…21 To investigate this, LSTN compositions with various A-site decient stoichiometries and with varying surface conditions were investigated with respect to the resulting morphology and microstructure aer a reduction for 2 h at 900 C in 5 vol% H 2 in Ar (Fig. 7).…”
Section: Materials Concept For Novel Sofc Anodesmentioning
confidence: 99%
“…Literature survey reports single phase LSTN compositions with Ni contents as high as 25 at%, which suggests that also higher contents of surface Ni could be obtained. 6 Microstructural reversibility and thermal stability of the Ni phase Neagu et al 5,21 have shown that exsolution of a metallic phase such as nickel from a titanate perovskite host matrix is possible and that this concept can be used to prepare nanoparticles on the surface. However, it was not shown that this material effect could be used in a reversible manner by reintegrating the metallic phase in the host titanate and to apply this effect repetitively, and on purpose, for microstructural and catalytic self-regeneration.…”
Section: Materials Concept For Novel Sofc Anodesmentioning
confidence: 99%
“…The recent work incorporated an alternative fuel electrode based on A-site deficient, nickel-doped perovskite La 0.43 Ca 0.37 Ni 0.06 Ti 0.94 O 3-γ into the SOFCRoll structure [4]. The LCNT is perovskite able to exsolve Ni nanoparticles and proved to be an excellent fuel electrode in high-temperature solid-oxide fuel cells (SOFC) [5]. For cell production, all tapes were cast on each other by sequential casting and co-sintered at 1350 °C [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by applying reducing conditions and energy to allow NPs to spontaneously exsolve from the substrate oxides and load on the surface. This method not only retains the bulk phase information on the substrate but also exsolves the NPs on the substrate oxides, thereby enhancing the interface connection between the NPs and the substrate surface, the exsolved arrangement reduces the likelihood of growth and agglomeration. However, the traditional high-temperature vapor phase reduction (HTVPR) process requires sufficient reduction time (10–72 h) and a high temperature (500–1300 °C) under a reducing atmosphere (such as H 2 , CO, and CH 4 ). The vapor-phase reaction process requires the gas to undergo diffusion at the three-phase interface for an extended period, and the high-temperature treatment enhances the gas diffusion of the relatively stable reducing atmosphere, thereby increasing the touching ratio between the gas and B-site metal ions. In addition, it is necessary to maintain a continuous supply of reducing atmosphere throughout the experimental process and continuous reaction to promote the exsolution of B-site ions to form NPs .…”
mentioning
confidence: 99%